175: EVALUATING THE PRINCIPLES IN WHICH THE DECISIONS ABOUT PIVOTAL MATTERS IN IRANIAN HEALTH SYSTEM ARE MADE. (8th February 2017) - Doshmangir, Leila; Rashidian, Arash
Abstract : Background and aims: This study aimed to evaluate the basis in which the decisions about pivotal matters in Iranian health system are made and how these decisions are in accordance with the best available evidence. Methods: To conduct this qualitative study, in the first step, four main issues with a high degree of importance, novelty and significant impact on health system were selected as follows: outsourcing clinical and Para-clinical services and health sectors to the private sector, global payment system to the hospitals and listing or delisting of pharmaceuticals from insurance coverage. In the next step, along with reviewing reports, documents and papers, semi-structured interviews were conducted with policymakers, experts and officials involved in the formulation and implementation of the selected issues. In the following step, a comprehensive search was carried out to find the research studies on the mentioned topics (fundamental evidence of policy-making). In the final stage, the results of the interviews and documentary analysis were compared with the best acquired evidence from the research studies. As a result, analytical model about decision making and interpretation method of evidence informed policy making in the health system were extracted. Results: In Iranian health system, evidence production is limited and the produced evidence is moderately applied in decision-making. Most decisions are made subconsciously, intuitively, fast, with low cognitive load and based on experiences. In recent years, due to the increasing number of researchers, awareness about modern methods of research and using evidence in decision-making is increasing gradually in the health system. Conclusion: Developing the importance and role of using evidence in making better decisions and policies for health managers and policy-makers and localizing global evidence are proper ways to enhance the use of evidence-informed decision-making approach in Iranian health system.